2015
DOI: 10.1002/2015jc010760
|View full text |Cite
|
Sign up to set email alerts
|

Combined infragravity wave and sea‐swell runup over fringing reefs by super typhoon Haiyan

Abstract: Super typhoon Haiyan struck the Philippines on 8 November 2013, marking one of the strongest typhoons at landfall in recorded history. Extreme storm waves attacked the Pacific coast of Eastern Samar where the violent typhoon first made landfall. Our field survey confirmed that storm overwash heights of 6–14 m above mean sea level were distributed along the southeastern coast and extensive inundation occurred in some coastal villages in spite of natural protection by wide fringing reefs. A wave model based on B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 56 publications
(69 reference statements)
7
79
1
1
Order By: Relevance
“…7, the correlation between W and c of all the obtained data is relatively weak while Shimozono et al [2015] shows clear negative correlation between W and c observed along the east of coast of Eastern Samar. According to Shimozono et al [2015], negative correlation between W and c is mainly because wider reef dissipates more wave energies through wave breaking and bottom frictions.…”
Section: Survey Results Of Inundation and Runup Heights In Batan And mentioning
confidence: 94%
See 1 more Smart Citation
“…7, the correlation between W and c of all the obtained data is relatively weak while Shimozono et al [2015] shows clear negative correlation between W and c observed along the east of coast of Eastern Samar. According to Shimozono et al [2015], negative correlation between W and c is mainly because wider reef dissipates more wave energies through wave breaking and bottom frictions.…”
Section: Survey Results Of Inundation and Runup Heights In Batan And mentioning
confidence: 94%
“…Both coasts of Batanes and Eastern Samar are fronted by a coral fringing reef, facing the deep Pacific Ocean and were dominantly affected by severe storm waves [Shimozono et al, 2015;Tajima et al, 2016]. Both Meranti and Haiyan migrated toward the WWN direction while the track of Meranti was about 6-8 • north from that of Haiyan as shown in Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Supported by post-typhoon survey reports (Bricker et al, 2014;Tajima et al, 2014), recent wave models (Roeber and Bricker, 2015;Shimozono et al, 2015), eyewitness accounts, and video footage (Mas et al, 2015;Bricker and Roeber, 2015), our findings suggest that a variety of hydrodynamic processes related to TC landfall must be considered when interpreting boulder deposits along coasts. These processes may include, in addition to incident (potentially very high) gravity waves and (or on top of) pressure-and wind-driven storm surge, meteo-tsunamis or seiches (Mori et al, 2014), as well as infragravity waves with periods of up to several minutes.…”
Section: Discussionmentioning
confidence: 99%
“…A Haiyan-related meteo-tsunami can be excluded due to a lack of bathymetric conditions with suitable resonance properties. Most recently, based on models simulating wave transformation over shallow fringing reefs using Boussinesq-type equations, Shimozono et al (2015) and Roeber and Bricker (2015) confirmed that the extreme run-ups and the bore-like flooding pattern in Eastern Samar must be explained by strong coupling of sea swells and infragravity waves with periods of > 1 min, which may have experienced excitation by resonances with the fringing reef (cf. Péquignet et al, 2009).…”
Section: Origin Of Exceptional Flooding Patternmentioning
confidence: 99%
See 1 more Smart Citation